2009
DOI: 10.1002/adfm.200900731
|View full text |Cite
|
Sign up to set email alerts
|

On the Synthesis of Carbon Nanofibers and Nanotubes by Microwave Irradiation: Parameters, Catalysts, and Substrates

Abstract: The microwave (MW)‐assisted synthesis of one dimensional carbon systems is introduced as a promising approach to improve the speed and cost‐effectiveness of the fabrication process. Improved reaction conditions are generated by direct MW heating and synthesis under advanced reaction conditions. The influence of the reaction conditions is investigated and the importance of individual process parameters on the synthesis is discussed. Temperature and pressure data recorded during the irradiation process are analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Microwave‐transparent substrates can be coated with a susceptor material to increase the heating efficiency and to decrease problems due to heat dissipation; for example, a metal layer, a coating of a conducting polymer, or an additional piece of silicon can be applied to enable CNT growth or the annealing of graphene on rather‐microwave‐transparent substrates; thus, without heating additives, the required elevated temperatures for the reaction could not be reached. Reaction vessels coated with silicon carbide or silicon carbide boards placed beneath a quartz vessel represent alternative approaches to increase the temperature rise of a microwave‐heated system.…”
Section: Fundamentals Of Heating Carbon Materials Using Microwave Irrmentioning
confidence: 99%
See 2 more Smart Citations
“…Microwave‐transparent substrates can be coated with a susceptor material to increase the heating efficiency and to decrease problems due to heat dissipation; for example, a metal layer, a coating of a conducting polymer, or an additional piece of silicon can be applied to enable CNT growth or the annealing of graphene on rather‐microwave‐transparent substrates; thus, without heating additives, the required elevated temperatures for the reaction could not be reached. Reaction vessels coated with silicon carbide or silicon carbide boards placed beneath a quartz vessel represent alternative approaches to increase the temperature rise of a microwave‐heated system.…”
Section: Fundamentals Of Heating Carbon Materials Using Microwave Irrmentioning
confidence: 99%
“…Druzhinina et al utilized a commercial single‐mode microwave reactor to grow multi‐wall CNTs and CNFs on different substrates, e.g., silicon, quartz glass, and mica. A quartz‐glass support was used to vertically place the catalyst‐coated substrate above a reservoir of liquid carbon source (Figure D).…”
Section: Preparation Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Thicker catalyst layers result on the other hand in general in large CNF diameter distributions. With spin-coated ethanolic nickel acetate layers thinner CNFs with smaller diameter distribution can be obtained, [ 17 ] but in return those CNF layers cannot be easily disassembled to free-standing fi lms. Moreover, it was observed that if no arching occurs, CNFs can just grow on top of the catalyst layer.…”
Section: Development Of a Growth Modelmentioning
confidence: 99%
“…[ 17 ] This method is based on the material-specifi c absorption of microwave is measured by an IR-sensor mounted outside the vial. Thus, it does not provide any information about the local temperature of the catalyst on the surface of the substrate.…”
Section: Free-standing Cnf Films Via Microwave-assisted Synthesismentioning
confidence: 99%